PENGEMBANGAN MODUL AJAR BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING, ART, MATHEMATICS (STEAM) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X - peny puji astuti (Cocos Bio, 2026)
Abstract: This study aims to determine the feasibility, practicality, and effectiveness of a Science, Technology, Engineering, Art, Mathematics (STEAM)-based teaching module to improve the creative thinking skills of Grade X students. This research and development employed the Borg & Gall model, conducted in six stages. The trial subjects in this research and development were a Biology teacher and students of SMAN 2 Selong, consisting of 30 Grade XI students and 32 Grade X students. Data collection techniques included interviews, questionnaires, and tests, while data analysis techniques used descriptive quantitative analysis. The results showed that the STEAM-based teaching module was very feasible, very practical and practical, as well as moderately or sufficiently effective to be used in the learning process. Feasibility was indicated by the average score obtained from material expert 1 of 95.6%, material expert 2 of 100%, and design expert of 96.3%, which are all categorized as very feasible. Practicality was indicated by the average score of teacher response questionnaires at 100%, which is categorized as very practical, and student response questionnaires at 78.77%, which is categorized as sufficiently practical. Effectiveness was shown by the average N-gain value obtained during the limited-scale trial, which was 0.59 and categorized as moderate or sufficiently effective. Based on the average score obtained from working on STEAM-based worksheets (LKPD), the result was 88.5, which is categorized as high or good. Keywords: Teaching Module, STEAM, Creative Thinking